Subsurface integrity studies on the drilling of Al/B4C/mica hybrid metal matrix composites. Issue 1 (2nd January 2020) - Eaben Rajkumar, S.; Palanikumar, K.; Pitchandi, K.; Latha, B.
ABSTRACT: When components are drilled for use in critical applications, some components might undergo surface defects and subsurface deformations. These defects arise due to microstructural and microhardness variations. This leads to sudden failure of these components. The present investigation focuses on Al/B4 C/Mica hybrid composites and Al/B4 C composites specimen with drilled surface and sub-surfaces. The goal is to identify measures to reduce surface integrity issues like microhardness, drilled surface morphology, and chip morphology on these specific components. Moreover, as a novel research, elemental and microstructural characterization of mica particles is carried out. The evaluation techniques used are Optical, EDX, SEM, and Vickers microhardness test. The stir cast specimens are drilled with process parameters of weight % B4 C and mica at specified cutting speed and feed rate. Tungsten carbide twist drill of 8 mm diameter is used. The investigation reveals that addition of mica particles causes reduction in the microhardness of drilled surfaces. The % of reduction observed is up to 13.7, 5.2 and 3 (in Hv ) on 4%, 8%, and 12% B4 C reinforced Al/B4 C/3%mica hybrid composites, respectively, in comparison with that of Al/B4 C composites.